Etika Bisnis Islam Pedagang Sapi dan Dampaknya Terhadap Kesejahteraan Pedagang di Kecamatan Masbagik Kabupaten Lombok Timur - Hulaimi, Ahmad (LIPI, 2016)
This study aims to determine the applied Islamic business ethics and its impact on the welfare of cattle traders in Masbagik sub-district, East Lombok regency. The research method used is descriptive qualitative research method with field research type (field research). The results of this study found that the study of Islamic business ethics applied by cattle traders in Masbagik Subdistrict has not fully applied the principles of Islamic business ethics, While from the study of the impact of Islamic business ethics on welfare, not all cattle traders in Masbagik sub-district, East Lombok regency Get Islamic prosperity because it has not fulfilled the needs of dharuriyat (prayer and haj). Much more has gotten a good life. Because it can meet the needs of dharuriyat. They have said to be happy, for being grateful for the well-being they received.